DIRECTIONS OF PLANNING AND CONDUCTING AUDIT OF INVENTORIES - Ovlayev Suhrob Temur o‘g‘li; Yo‘lchiyev Oybek Ulug‘bek o‘g‘li; Normo‘minova Dilorom Umar qizi; Avlayeva Oybarchin Olim qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article describes the directions of planning and conducting an audit of inventories. As a result of the study, proposals for improving the audit of inventories were developed.